Exploring injury assessment using motion tracking technology and ergonomic tools in archery performance - Ji, X.; Arzalluz, I. A.; Gao, X. G.; Tamimi, Z. A.; Swierski, E.; Swierski, E.; Piovesan, D. (Frontiers in Medical Engineering, 2024)
Introduction: Archers face a notable annual risk of injury attributed to the repetitive strain exerted on their upper body muscles and joints. This groundbreaking study marks the first utilization of real-time motion tracking combined with ergonomic analysis in archery research, eliminating the need for extensive equipment setups and streamlining data collection.